2004
DOI: 10.1080/13697130410001713779
|View full text |Cite
|
Sign up to set email alerts
|

How menopause affects the lives of women in suburban Chandigarh, India

Abstract: Although north Indian women experienced various symptoms at menopause, they largely ignored these, while welcoming the freedom from menstruation-related worries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
43
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 7 publications
11
43
1
2
Order By: Relevance
“…This showed that the women from the lower socio-economic status had attained menopause at earlier ages. The frequencies of the menopausal symptoms in our study population were much higher than those which were found in several other studies [11][12][13]. A study which was conducted in Pune showed a loss of interest (in 93% women), pressure/tightness in the head (in 83% women), weight gain (in 67% women) and hot flushes (in 54% women) as the common symptoms in decreasing frequency [14].…”
Section: Discussioncontrasting
confidence: 61%
“…This showed that the women from the lower socio-economic status had attained menopause at earlier ages. The frequencies of the menopausal symptoms in our study population were much higher than those which were found in several other studies [11][12][13]. A study which was conducted in Pune showed a loss of interest (in 93% women), pressure/tightness in the head (in 83% women), weight gain (in 67% women) and hot flushes (in 54% women) as the common symptoms in decreasing frequency [14].…”
Section: Discussioncontrasting
confidence: 61%
“…Natural and Surgical Menopause: More women suffered hot flushes following the hysterectomy compared to those who had natural menopause [(55/67 (82%) vs. 75/110(68%) p < 0.05)]. We also observed higher hysterectomy rate (14%) amongst the urban educated women attending our menopause clinic compared to 5.8 % in semi urban India [5]. 28.9% of women were individualized to receive different types of hormone therapies including Soya -isoflavones for various menopause related morbidity at any given point of time in our group.…”
Section: Discussionsupporting
confidence: 61%
“…are derived from UNDP reports and various other studies as mentioned in the reference section. For India which is a developing country with non-homogeneous population, comparative values for cohort groups e.g., rural, semiurban or urban-metro cities have been derived using data from the present study as well as from the published work [1,2,5,6,8,9,16,[24][25][26][27]. The general profile of our economically privileged & medically insured middle aged urban (METROPOLITAN) women showed a very high literacy rate of 93% with 36% university graduates as compared to the national female literacy rate of 54% (urban vs. rural :73 vs. 46).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations